Understanding hand sign language in human-computer interaction - Tai, Hwee Peng (2009)
Communication is one of the most important parts of human life. Deaf people are unable to communicate using speech and they are resorted to use gesture communication. Over the years, deaf people developed a system for them to communicate and this is known as Sign Language today. However, only deaf people uses this communication system and this has created a barrier between the deaf and others. Deaf children, in particular, face various difficulties in the development of reading and communication skills, which are mostly linked with their poor language experiences when they arrive in school. They have limited access to language from young; hence communication with their surroundings is only achieved after significant effort. In this project, a new educational software named “Let’s Talk” is developed to improve and enhance the literacy skills of deaf or hard of hearing people. Specifically, this project looks into the translation from English to ASL with the help of 3D animation. It also uses speech recognition and text to speech to make the software useful for normal people to communicate with person who signs, but does not hear. It is also useful for blind people to communicate with the deaf, thus removing the communication barrier between the deaf and others. “Let’s Talk” can prove to be a useful learning object that contributes to the deaf and hard of hearing.